Night Capture of Roosting Cave Birds by Neanderthals: An Actualistic Approach - Blanco, Guillermo; Sánchez-Marco, Antonio; Negro, Juan José (Frontiers in Ecology and Evolution, 2021)
Evidence is accumulating on the regular and systematic Neanderthal exploitation of birds. However, the motivations, mechanisms, and circumstances underlying this behaviour remains little explored despite their potential implications on Neanderthal ecology and capabilities. Fossil remains of choughs (Pyrrhocorax, Corvidae) are among the most abundant in cave sites with Mousterian technology. We reviewed the evidence showing that Neanderthals processed choughs for food, and confirmed that it occurred frequently over a widespread spatial and temporal scale. This lead us to propose the hypothesis that the cave-like refuge is the keystone resource connecting Neanderthals and choughs captured at night in rocky shelters eventually used by both species. By adopting an actualistic approach, we documented the patterns of refuge use and population dynamics of communally roosting choughs, the strategies and technology currently used to capture them, and their behavioural response against experimental Human predators at night. Actualistic experiments showed that large numbers of choughs can be captured without highly sophisticated tools at night regularly and periodically, due to their occupation year-round during long-term periods of the same nocturnal shelters, the constant turnover of individuals, and their high site tenacity at these roost-sites even after recurrent disturbance and predation. Captures even with bare hands are further facilitated because choughs tend to flee confused into the cavity in darkness when dazzled and cornered by human (experimental) predators. Given the extreme difficulty of daylight chough capturing in open country, nocturnal hunting with the help of fire in the roosting caves and consumption in situ are proposed as the most plausible explanations for the strong association of choughs and Neanderthals in fossil assemblages. Night hunting of birds has implications for the social, anatomical, technological, and cognitive capacities of Neanderthals.